The impact of Home Parenteral Nutrition on the lives of adults with Type 3 Intestinal Failure. (April 2018) - Heaney, Alice; McKenna, Stephen P.; Wilburn, Jeanette; Rouse, Matthew; Taylor, Michael; Burden, Sorrel; Lal, Simon
Summary: Background & Aims: Several studies have been published reporting on the impact of Home Parenteral Nutrition (HPN) on the lives of people with Type 3 Intestinal Failure. These studies focused on symptoms and functional limitations resulting from the treatment. The aim of this study was to determine how dependence on HPN affects individuals' ability to fulfil their human needs. Methods: Unstructured qualitative interviews were conducted with people dependent on HPN, who were asked to explain how their lives were affected by the treatment. Theoretical thematic analysis was conducted on the interview transcripts to identify statements describing aspects of human needs that were left unfulfilled. Care was taken to separate the impact of HPN from that of the underlying disease. Results: Interviews were conducted with 30 patients (53% female; mean age, 55.9 (range 35–76) years). Most of the sample (87%) had short bowel syndrome. Major aspects of need affected by HPN were related to: autonomy, cognition, relationships, role fulfilment, socialisation, appearance and self-esteem, appetite and perceived vulnerability. Conclusions: The study illustrates how patients' lives are affected by HPN. Statements generated from this qualitative study were used to produce the Parenteral Nutrition Impact Questionnaire (PNIQ), a patient-centric measure of quality of life specific to people using HPN. Highlights: HPN, while life-saving, imposes restrictions on the lives of patients. Quality of life is reduced because HPN prevents the fulfilment of basic human needs. Needs impaired include autonomy, role fulfilment, esteem, attractiveness and safety.